Patient Safety Interprofessional Training for Medical, Nursing, and Pharmacy Students - Anne C. Gill; Jennifer B. Cowart; Catherine L. Hatfield; Rita A. Dello Stritto; Peggy Landrum; Nadia Ismail; Elizabeth A. Nelson; Cayla R. Teal (Association of American Medical Colleges, 2017)
Introduction Patient safety education is required in medical, nursing, and pharmacy training, and interprofessional education offers an ideal format for teaching the core concepts of patient safety. This training activity was developed to fulfill interprofessional education core competencies for communication and teamwork and was nested within a required patient safety course taught at a medical school. However, the activity can easily be adapted as a stand-alone offering that can be included in a preclinical doctoring course, offered as an elective, or hosted at a college of nursing or pharmacy. Our goal was to prepare learners for the clinical environment by providing a context for patient safety, communication, and teamwork. Methods Students participate in a 1.5-hour large-group activity that explores a case from the perspectives of each discipline. Faculty from all three disciplines sequentially present and debrief the case using focused questions to guide students' reflections and interactions between team members. Results We have presented this activity for 4 consecutive years. Students complete a questionnaire with retrospective pre-post ratings of their perspectives on the activity and its impact on their awareness of disciplinary roles and responsibilities, communication errors, and strategies for addressing interdisciplinary conflicts. Results show statistically significant increases in the items of interest. Discussion This interprofessional education offering is effective in terms of increasing awareness and knowledge among members of three health care disciplines, improving awareness of potential kinds of communication errors, and helping students consider the role of interdisciplinary interactions.